2013
DOI: 10.1007/s11481-013-9464-6
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Tyrosine 470 of Human Dopamine Transporter is Critical for HIV-1 Tat-Induced Inhibition of Dopamine Transport and Transporter Conformational Transitions

Abstract: HIV-1 Tat protein plays a crucial role in perturbations of the dopamine (DA) system. Our previous studies have demonstrated that Tat decreases DA uptake, and allosterically modulates DA transporter (DAT) function. In the present study, we have found that Tat interacts directly with DAT, leading to inhibition of DAT function. Through computational modeling and simulations, a potential recognition binding site of human DAT (hDAT) for Tat was predicted. Mutation of tyrosine470 (Y470H) attenuated Tat-induced inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
117
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(131 citation statements)
references
References 56 publications
11
117
3
Order By: Relevance
“…It can penetrate the blood brain barrier and convert to toxic MPP + under the action of monoamine oxidase B. MPP + is very similar to dopamine in chemical structure, and can act on SNpc through dopamine transporter to further recruit MPP + to the mitochondria; thus, impeding the role of respiratory chain enzyme complex I, energy crisis, and cell death (Midde et al, 2013;Velázquez-Sánchez et al, 2013;Dehnes et a., 2014;Schwarz et al, 2014). Additionally, MPP + is able to inhibit the activity of tyrosine hydroxylase, thus reducing the synthesis of dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…It can penetrate the blood brain barrier and convert to toxic MPP + under the action of monoamine oxidase B. MPP + is very similar to dopamine in chemical structure, and can act on SNpc through dopamine transporter to further recruit MPP + to the mitochondria; thus, impeding the role of respiratory chain enzyme complex I, energy crisis, and cell death (Midde et al, 2013;Velázquez-Sánchez et al, 2013;Dehnes et a., 2014;Schwarz et al, 2014). Additionally, MPP + is able to inhibit the activity of tyrosine hydroxylase, thus reducing the synthesis of dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…Prepulse inhibition is known to be attenuated by dopamine agonists in mice, particularly those with preference for D1-like receptors [46]. Tat is known to allosterically modulate the dopamine transporter [47], elevating synaptic dopamine concentrations [48] and increasing the efficacy of binding ligands [49]. Tat-induced enhancement of dopamine levels could further promote the deficits observed in PPI presently.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced DA transporter (DAT) levels in the putamen and ventral striatum are found in HIV-1+ individuals with cognitive impairment (Wang et al 2004; Chang et al , 2008). In vitro studies have shown that DAT is targeted by HIV-1 proteins Tat and gp120, resulting in transporter impairment (Aksenov et al 2008; Ferris et al 2009; Midde et al 2013; Zhu et al 2009; Zhu et al 2011), due to direct protein-protein interactions (Zhu et al 2009) involving an allosteric modulation of DAT by the Tat protein (Zhu et al 2011). In addition, DA-dependent signaling has been identified as a mechanism of HIV-1 protein neurotoxicity (Aksenova et al 2006; Silvers et al 2007; Wallace et al 2006).…”
Section: Discussionmentioning
confidence: 99%